Resistência na poesia feminista : uma análise dos escritos de Rupi Kaur, Amanda Lovelace e Ryane Leão - Barros, Michelle Leite de (2023)
A study is made on the poems written on the social network Instagram, which we call insta-poems, aimed precisely at the poets Rupi Kaur, Amanda Lovelace e Ryane Leão. Because they are inserted in their own culture and bring the most diverse experiences as women, situations commonly faced in the daily life of the three authors are exposed, such as machismo, racism, fatphobia, etc., and can be presented by what they write in their poems. The study also focuses on the works published by the poets, in the case of Rupi, the chosen ones were milk and honey (2014), the sun and her flowers (2017), home body (2020); those of Amanda, the princess saves herself in this one (2016), the witch doesn’t burn in this one (2018), the mermaid’s voice returns in this one (2019); finally, Ryane, who has two books published and both were recognized: Tudo nela brilha e queima (2017) and Jamais peço desculpas por me derramar (2019). The presente work goes through the history of feminism, exposing some events that led women to pursue their rights in the search for gender equality. It is inferred to discuss the intersections covered by the movements in order to understand different life experiences, as happens when talking about Decolonial Feminism. Thus, we achieved that it is necessary to understand what it is to be a woman in a patriarchal society aimed at shaping people’s thoughts and their behaviors, and how much this fact affects the female gender, aspects of which we see at this moment through the writings of Rupi, Amanda and Ryane.